Outcomes of the Boston Type I Keratoprosthesis as the Primary Penetrating Corneal Procedure. Issue 11 (November 2018) - Driver, Todd H.; Aravena, Carolina; Duong, Huong N.V.; Christenbury, Joseph G.; Yu, Fei; Basak, Samar K.; Aldave, Anthony J.
Abstract : Purpose: To report the outcomes of the Boston type I keratoprosthesis (KPro) as the primary penetrating corneal procedure. Methods: In this retrospective review of all KPro procedures performed by 2 surgeons from May 1, 2004, to December 31, 2015, indications and outcomes were compared between KPros performed as the primary keratoplasty procedure (primary KPro) versus after failed keratoplasty (previous keratoplasty). Results: A total of 262 KPros were implanted in 231 eyes, including 67 primary KPro procedures. The most common indications for primary KPros were corneal scarring/vascularization (43%), Stevens–Johnson syndrome (22%), and chemical/thermal injury (22%). Although preoperative corrected distance visual acuity (CDVA) was similar in the 2 groups ( P = 0.36), a significantly higher proportion of the eyes in the primary KPro group had a CDVA ≥ 20/200 each of the first 4 years after surgery (all P ⩽ 0.023). The most common postoperative complications in the primary KPro and previous keratoplasty groups were retroprosthetic membrane (40% vs. 51%, P = 0.15), persistent epithelial defect (37% vs. 24%, P = 0.05), and elevated intraocular pressure, which was the only complication significantly more common in either group (31% vs. 18%, P = 0.03). No difference in KPro retention was observed between the 2 groups ( P = 0.63). Conclusions: In the setting of preexisting ocular comorbidities in which PK is associated with poor outcomes and KPros have been associated with an increased incidence of postoperative complications, primary KPro is associated with significantly greater % of eyes with CDVA ≥ 20/200 in the first 4 years. However, given a significantly higher incidence of postoperative intraocular pressure elevation in these eyes, longer follow-up is needed to determine whether the difference in CDVA is maintained. Abstract : Supplemental Digital Content is Available in the Text.